Seed Coating with Biological Agent to Increace Plant Growth and Yield of Rice - Palupi, Tantri; Ilyas, Satrias; Machmud, Muhammad; Widajati, Eny (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
Seed quality is an important factor in rice production. Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is a seedborne disease of rice that cause serious yield losses in Indonesia. Experiments were conducted at the Laboratory of Rice Research Babakan, IPB, Bogor; Laboratory of Seed Science and Technology at IPB, Bogor; and the Laboratory of Seed PT. EWSI, Purwakarta, from April to August 2011. The objective of this research was to determine the effectiveness of coating Xoo contaminated rice seeds with biological agents on plant growth and crop yield. The experiments were arranged in a randomized complete block design with one factor (seed coating treatment),i.e. T0 = negative control, healthy seed; T1 = positive control, the seeds contaminated with Xoo; T2 = P. diminuta A6 and B. subtilis 5/B; T3 = alginate 3% + 1% peat + P. diminuta A6 and B. subtilis % 5/B; T4 = arabic gum 3% + 1% gypsum + P. diminuta A6 and B. subtilis 5/B; T5 = CMC 1.5% + 1% talc + P. diminuta A6 and B. subtilis 5/B, and T6 = bactericide streptomycin sulfat 4%. The results showed that seed coating treatment with with 3% alginate + 1% peat + P. diminuta A6 + B. subtilis 5/B was the best treatment based on the percentage of full and empty grain weight per panicle, and the percentage of number of full and empty grains per panicle.